Pharmacologic venous thromboembolism prophylaxis is not associated with post sphincterotomy bleeding after endoscopic retrograde cholangiopancreatography. Issue 6 (June 2021) - Krill, Timothy; Li, Dongming; Sood, Akhil; Baliss, Michelle; Abrol, Robinder; Zaibaq, Jenine; Parupudi, Sreeram
Abstract: Background/Aim: Endoscopic sphincterotomy is considered high risk for post-procedure bleeding. Sphincterotomy in patients on therapeutic anticoagulation is avoided given increased bleeding risk. There is minimal data on the risk of post-sphincterotomy bleeding (PSB) among those on prophylactic anticoagulation for venous thromboembolism (VTE) prophylaxis. Methods: We performed a retrospective case control study of all inpatient endoscopic retrograde cholangiopancreatographies (ERCPs) with a sphincterotomy at our institution between July 2016 to February 2020. Cases were divided into two groups based on administration of peri‑procedural pharmacologic VTE prophylaxis. The outcomes were the rates of PSB and VTE within 30-days of the ERCP. Results: A total of 369 inpatient ERCPs with a sphincterotomy were identified. 151 cases received peri‑procedural pharmacologic VTE prophylaxis and 218 did not. The mean Padua score and American Society of Anesthesiologists physical status classification were significantly greater in the prophylaxis group. PSB was statistically similar between both groups (3.3% vs. 5.5%, p =.32). VTE was statistically similar (0.7% vs. 0.5%, p =.79). Multivariate analysis did not reveal an association between PSB and peri‑procedural pharmacologic VTE prophylaxis. Conclusion: Peri-procedural pharmacologic VTE prophylaxis is not associated with increased rates of PSB. These findings suggest that pharmacologic VTE prophylaxis can be safely continued in those undergoing an endoscopic sphincterotomy.